The improvement of grape juice quality using Thermomucor Indicae-Seudaticae pectinase - de Carvalho Tavares, Iasnaia Maria [UNESP] (2020)
The effect of pectinolytic enzyme preparation (PEP) produced by the fungus Thermomucor indicae-seudaticae-N31 (PEP-N31) on total phenolic content, concentrations of methanol and color of grape juice was studied. Positive results were found when PEP-N31 was used to extract phenolic compounds after the grapes had been blanched for 3 min and macerated for 1 h. The resulting juice had better yield, color characteristics and higher phenolic content (1637.21 mg.L-1, as gallic acid equivalent, or GAE) than the conventionally prepared juice (1422.59 mg GAE.L-1), and it was very similar to the juice obtained through the treatment with a commercial enzyme (1682.10 mg GAE.L-1). The concentration of methanol in the juice produced with the PEP-N31 was less than 200 mg.L-1. These results encourage the use of PEP produced by Thermomucor indicae-seudaticae-N31 by the grape-processing industry.